Coleopteros cerambicidos xilofagos del Parque Chequeño Seco (Argentina) - Fiorentino, D.C.=700 1 Bellomo, V.; Diodato, L.; Notario, A.; Castresan, L.
(En, Es)
ilus., 5 ref.
Keywords: CERAMBYCIDAE; PLAGAS FORESTALES; ARGENTINA